A New Kind of Relevance for Archaeology - Ortman, Scott G. (Frontiers in Digital Humanities, 2019)
Traditional ways of doing archaeology impact the world in a variety of ways, but despite recent efforts the practical relevance of archaeology has remained limited. In this paper, I discuss why this is the case and suggest how archaeology can achieve greater practical relevance. I argue, first, that the traditional focus of archaeology on reconstructing the past is valuable but is unlikely to expand its practical relevance because the results are too context-specific. Second, I suggest traditional responses to the problem of historical contingency are also inadequate because the results are too general to connect to the specific issues and solutions society needs. Finally, I make a surprising and perhaps radical suggestion: that a productive way forward is to resuscitate and reformulate elements of the New Archaeology that were never realized by its proponents. I use the example of settlement scaling theory to illustrate that this is both possible and productive, and that additional work in this spirit would enhance the practical relevance of our field.